Inflammatory biomarkers for prediction of sepsis in febrile patients - Tay, Siow Phing; Wong, Jin Shyan; Lau, Chuan Joon; Alice, Joe; Vanessa Claudia, Musa; Arni Nazera, Azahar; Henry Rantai, Gudum (2025)
Introduction: Sepsis, an infection-induced systemic inflammatory response syndrome, has high morbidity and mortality rates. Rapid recognition of sepsis with appropriate management saves lives. Blood cultures remain the gold standard diagnostic tool, results that are only available after 24-48 hours have hampered the effort of minimising mortality in sepsis care. Several inflammatory biomarkers have emerged as new rapid tools, but large discrepancy exists in their reported diagnostic values. Materials & Methods: This retrospective study investigated the clinical significance of white blood cells (WBC), absolute neutrophil count (ANC), platelet count (PLT), procalcitonin (PCT), C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) in prognosticating sepsis. Results & Discussion: From 814 febrile cases with blood cultures done, prevalence of sepsis was 9.8% with 12.5% mortality. Majority (57.5%) grew Gram negative cultures with Escherichia coli being the most common isolates. Occurrence of sepsis was significantly associated with older age. Significantly higher ANC, PCT, CRP and lower PLT were observed in septic patients. PCT was superior to the others in terms of diagnostic accuracy (85% sensitivity, 55% specificity). Multivariate analysis by combining all six biomarkers with age revealed that PCT (OR: 1.032; 95%CI: 1.013-1.051; p=0.001) and CRP (OR: 1.005; 95%CI: 1.001-1.008; p=0.006) were the only two significant biomarkers for prediction of sepsis (86.5% accuracy). Conclusion: This study demonstrated the significant role of PCT in diagnosing and predicting sepsis. In cases where sepsis is suspected, PCT should be included in the test panel to allow rapid detection of sepsis that requires prompt clinical intervention to ensure better outcome.